Some Features of Intuitionistic L- R1 Spaces - Islam, R.; Hossain, M. S. (Journal of Scientific Research, 2018)
In this paper, we have introduced four notions of R1 space in intuitionistic L-topological spaces and established some implications among them. We have also proved that all of these definitions satisfy “good extension” and “hereditary” property. Finally, it has been shown that all concepts are preserved under one-one, onto and continuous mapping.